PERAN KEPUASAN NASABAH DALAM MEMEDIASI PENGARUH CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH - Nova Ch. Mamuaya; Bertha I. Mundung (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to determine the role of customer satisfaction in mediating the influence of customer relationship marketing on customer loyalty at Bank SulutGo Manado City. The sample of this study was 100 people, the data collection technique used a questionnaire with a Likert Scale and Path Analysis techniques for data analysis. The results show that customer relationship marketing has a significant effect on customer satisfaction, customer relationship marketing has a significant effect on customer loyalty and customer satisfaction has a significant effect on customer loyalty. The results also show that customer satisfaction mediates effect of customer relationship marketing on customer loyalty